STRATEGI KOMUNIKASI PEMASARAN PADA CLOTHING BRAND YEOBOSEYO.ID - Prakoso, Galung; Gaby Swastika (Jurnal Spektrum Komunikasi, 2024)
The continuous growth of internet users in Indonesia since 2012 has had an impact, particularly on the use of social media. In 2023, 60.4% of the population in Indonesia was using social media. Instagram and TikTok are widely used for social networking and business marketing, including by the clothing brand Yeoboseyo.id. This study aims to examine the marketing communication strategies of Yeoboseyo.id from September 2023 to February 2024, using a quasi-qualitative method with semi-structured interviews and triangulation techniques for data validity. The results show that Yeoboseyo.id utilizes a marketing communication mix, including advertising on social media, conducting sales promotions by providing vouchers, freebies, and giveaways, and implementing public relations to maintain brand reputation. They also engage in personal selling to build consumer trust and direct marketing through one-step and two-step approaches to increase sales and maintain relationships with consumers. The conclusion of this study is that Yeoboseyo.id has effectively implemented its marketing communication strategy; however, there are still some areas that are not fully optimized, including the use of below-the-line promotion channels and the implementation of personal selling.